Comparison of changes in etiologic microorganisms causing early-onset neonatal sepsis between preterm labor and preterm premature rupture of membranes*. (2nd November 2015) - Jeong, Heejeong; Han, Su-jin; Yoo, Ha-Na; Choi, Suk-Joo; Oh, Soo-Young; Kim, Yae-Jean; Roh, Cheong-Rae; Kim, Jong-Hwa
Abstract: Objective : To investigate changes in the etiologic microorganisms causing early-onset neonatal sepsis (EONS) in preterm labor (PTL) or preterm premature rupture of membranes (pPROM) cases over the past 16 years and to analyze the associated factors. Methods : We included consecutive singleton pregnancies delivered before 34 weeks due to PTL or pPROM. The etiologic microorganisms causing EONS in PTL and pPROM cases were compared between period 1 (1996–2004) and period 2 (2005–2012). Results : There was no difference in the incidence of Gram-positive bacteria causing EONS between period 1 and 2, either in PTL (2.0% versus 2.1%, p  = 1.0) or in pPROM (1.5% versus 1.6%, p  = 1.0). However, the incidence of EONS caused by Gram-negative bacteria was significantly increased in pPROM (0.6% versus 2.7%, p  = 0.040) during period 2, compared to period 1; but not in PTL (0.3% versus 1.2%, p  = 0.211). Multivariable analysis revealed that a prolonged ROM-to-delivery interval (>7 d) was significantly associated with EONS caused by Gram-negative bacteria in pPROM (odds ratio: 6.6, 95% confidence interval: 1.4–31.8, p  = 0.018). Conclusions : The etiologic microorganisms causing EONS have changed over the past 16 years in pPROM cases but not in PTL cases.